Therapeutic Community for Victims of Narcotics Abuse at the Mutiara Abadi Binjai Rehabilitation Center, Bandar Senembah Village, Binjai Barat District-Binjai City (Analysis of PP. Number 25 of 2011 and Maqashid Al-Syari'ah) - Hamdan Mubarok; Zulkarnain Zulkarnain; Hafsah Hafsah (DE LEGA LATA: JURNAL ILMU HUKUM, 2023)
This study aims: (1) To find out PP No.25 of 2011 regulates rehabilitation in the Therapeutic Community approach, (2) To find out Therapeutic Community at the Mutiara Abadi Binjai Rehabilitation Center based on PP No.25 of 2011, (3). To find out the Therapeutic Community at the Mutiara Abadi Binjai Rehabilitation Center in terms of Maqashid Al-Syari'ah. This research is a field research that uses empirical juridical methods. This research approach is statutory, case approach, conceptual approach. The sources of this research are primary data sources obtained directly from the original sources in the form of interviews, opinion polls from individuals or groups (people) and secondary data obtained through intermediary media or indirectly in the form of books, notes, existing evidence, or archives, both published and unpublished. The results of this study are the results of assessments and Ministerial Regulations", almost all of which are used as a reference by the Therapeutic Community as a method in the rehabilitation process such as the initial stage (induction) after undergoing detoxification, the primary stage (a social rehabilitation program of about 4 months), the re-entry stage. (facilitating residents to be able to socialize with outside life for 3-6 months. It's just that there are programs that are typical of the Therapeutic Community, namely the after care stage (friendship among former residents outside the orphanage), Therapeutic Community which is held at the Mutiara Abadi Rehabilitation Center Binjai also does not deviate from the provisions of the articles contained in PP No. 25 of 2011, such as the pattern of resident coaching, availability of infrastructure, medical and social rehabilitation, the Therapeutic Community approach at the Mutiara Abadi Binjai Rehabilitation Institution from the perspective of Maqashid Al-Syari' Ah, all achieved in terms of benefit as discussed in Maqashid Al-Syari'ah, especially on the five main principles that must be realized such as, hifzh ad-dn (maintaining religion), hifzh an-nafs (maintaining), hifzh al-'aql (maintaining reason), hifzh an-nasl (maintaining offspring), and hifzh al-ml (maintaining wealth).